Seni Pertunjukan Ketoprak Sebagai Sumber Ide Perancangan Background Film Animasi Lakontara Pada Kompetisi GEMASTIK XV Tahun 2022 - Paramarta, Cahyaning Brian; Kurniawan, Rendya Adi (ISI Press Institut Seni Indonesia Surakarta, 2023)
The performing arts of Ketoprak is one of Indonesia’s cultural arts which is currently experiencing a decline in interest due to globalization and the rapid development of technology that has influenced the tastes of modern society in choosing entertainment. Ketoprak art competition with modern art has an impact on the unpreparedness of art workers to respond to the challenges of the times in order to provide creative, innovative, and attractive presentations. So that the urgency in this research is the art of Ketoprak which has experienced a decline in prestige and minimal conservation efforts that threaten the existence of this art. The design of this background aims to complement the visual assets in the Lakontara 2D animation which is contested at the Pagelaran Mahasiswa Nasional Bidang Teknologi Informasi dan Komunikasi (GEMASTIK) XV 2022. The method used is primary and secondary data collection, as well as for the design using the animation pipeline method from pre-production to production.